Mapping temperature decline in beef cattle during conventional chilling - Klauer, Brenna Lynne, author; Woerner, Dale R., advisor; Belk, Keith E., committee member; Nair, Mahesh N., committee member; Bonanno, Alessandro, committee member (Colorado State University. Libraries, 2019)
A continued increase in beef carcass weights has likely caused need to adjust chilling practices in order to chill carcasses appropriately with respect to food safety and beef quality. The objectives of this study were to track continuous temperature decline of beef carcasses of varying size, gain insight on how fat thickness and carcass size affect overall chilling rates, and to model temperature decline in deep muscle tissue of 6 muscles and one beef carcass surface location. Temperature recorder thermocouples were placed in 7 carcass locations and temperature was measured every 30 seconds from post electrical stimulation until the carcasses were removed from the postmortem chilling coolers (hot boxes) to be graded. Carcass temperatures were measured at the geometric center of the 1) brisket/plate (deep pectoral), 2) deep chuck (medial side of scapula/clod heart), 3) deep tissue (Semimembranosus), 4) Gluteus medius (Sirloin), 5) Longissimus dorsi at the 12th rib, 6) surface (5mm under the fascia) at the 11th rib, 7) Psoas major (Tenderloin), and 8) ambient per group of carcasses. Carcasses were classified into groups consisting of (1) light (650- 750 pounds), (2) medium (850-950 pounds), and (3) heavy (1050 to 1150 pounds) hot carcass weights. Surface temperatures from all weight categories reached levels below 4˚C within 24 hours of chilling. In the deep tissue (SM), Gluteus medius, and Longissimus dorsi carcass locations, differences in temperature between light versus medium and heavy weight ranges at the final hour of chilling (hour 28) were detected (P < 0.05). At hour 28, no differences (P ≥0.05) were detected among surface, deep pectoral, Psoas major, or deep chuck locations. At hour 28, light weight carcasses reached below the recommended chilling target of 7˚C in the deep tissue location; however, the medium and heavy range carcasses never declined below 7˚C. When larger carcasses are not chilled adequately, potential quality implications exist including reduced quality grades, increased carcass weight loss due to shrink, and fabrication issues. Therefore, beef processing facilities should consider sorting cattle before chilling in order to maximize the quality of the products being processed.
Keywords: carcass size; beef; conventional chilling